ANALISIS KADAR VITAMIN C DALAM BERBAGAI JENIS RIMPANG KUNYIT (Curcuma spp.) ASAL GARUT DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Dani Sujana (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Curcuma spp. consists of several species including temulawak (C. xanthorriza), turmeric (C. domestica), white ginger (C. zedoaria), and black ginger (C. aeruginosa). Likewise, it is known that the bioactive compound of turmeric rhizome is ascorbic acid (vitamin C). There are several methods developed to determine vitamin C levels, one of which is the UV-Vis spectrophotometry method. The research design used was descriptive experimental with the aim of knowing the levels of vitamin C in some Curcuma spp. growing in the Garut, Indonesia. This research uses UV-Vis Spectrophotometry method. From the results of this study, it has been reported that Curcuma xanthorriza has the highest levels of vitamin C compared to the others, namely the levels obtained are 0.720 mg/100 g.